Two new species of Eleutherodactylus (Anura: Leptodactylidae) from the Andes of northern Peru - Duellman, William E.; Lehr, Edgar; Venegas, Pablo J. (Zootaxa, 2006)
Two new sympatric species assignable to the Eleutherodactylus orestes Group were discovered in the northern part of the Cordillera Central of the Andes in northern Peru. One of the new species differs from all other members of the group by having conical tubercles on the eyelids and heels; the other species differs by having a white groin with brown marks.